THE ADDITIVE EFFECT OF PAPAYA LEAF EXTRACT (Carica papaya L) ON DRINKING WATER ON THE ORGANOLEPTIC QUALITY OF JOPER CHICKEN MEAT - A., LESTARIANTO; SRIYANI, N. L. P.; DEWI, G. A. M. K. (Majalah Ilmiah Peternakan, 2022)
This research aims to determine the effect of papaya leaf extract (Carica papaya L) added to drinking water and the organoleptic value of joper chicken meat. This research was conducted at the Laboratory of Animal Product Technology and Microbiology, Faculty of Animal Husbandry, Udayana University for 2 months from February to March 2021. This research used a complete random design (CRD) with 4 treatments and 4 replications assessed by 20 semi-trained panelists. The data were processed by non parametric kruskall wallis test if there was a significant differences, it was followed by man witney. The four treatments were: papaya leaf concentration as much as 0 ml as a control (P0), papaya leaf concentration as much as 25 ml (P1), papaya leaf concentration as much as 30 ml (P2), papaya leaf concentration as much as 35 ml (P3). The variables observed were the organoleptic test which included color, aroma, texture and tenderness, flavour, bitterness level, and total acceptance. The results showed that the effect of adding papaya leaf extract (Carica papaya L) to drinking water had a significant effect (P <0.05) on color, aroma, texture and tenderness, flavour, bitterness level, and total acceptance. The conclusion of this research is the addition of papaya leaf extract to drinking water which can affect the organoleptic quality of joper chicken meat. The optimal concentration of papaya leaves to produce good organoleptic quality is 30 ml, with sensory criteria of golden brown color, fishless aroma, increased tenderness and absence of bitter taste in meat.